Chk1 inhibition-induced BRCAness synergizes with olaparib in p53-deficient cancer cells. Issue 2 (17th January 2023) - Zhao, Yang; Zhou, Kehui; Xia, Xiangyu; Guo, Yajie; Tao, Li
ABSTRACT: Although targeting DNA-damage repair by inhibition of PARP exhibits weak or modest single-agent activity due to the existence of functional BRCA1/2 alleles, PARP inhibitors have been gradually applicable in BRCA-proficient cancers. Checkpoint kinase 1 (Chk1) inhibition selectively disrupts homologous recombination (HR)-mediated DNA repair and confers synthetic lethality in p53-deficient tumors, we therefore aim at expounding the chemopotentiating effects of Chk1 inhibition on PARPi in BRCA-proficient and p53-deficient cancer cells. Initially, BRCA wild-type, p53-null cells including AsPC-1 and H1299 demonstrated innate resistance to PARP inhibitor olaparib compared to BRCA1-mutant, p53-null MDA-MB-436 cells. We quantified the interaction between olaparib and a selective Chk1 inhibitor MK-8776, which produced synergistic effects under sub-IC50 concentrations in p53-depleted AsPC-1 and H1299 cells. Olaparib in combination with MK-8776 showed enhanced antitumor effects through prohibiting proliferation and secondarily inducing apoptosis in two cell lines. Of note, we observed that MK-8776 significantly sensitized cells to olaparib by broad DNA and chromosomal breaks. Mechanistically, MK-8776 abrogated olaparib-induced BRCA1 intranuclear foci formation, MCM7-mediated replication machineries, and ultimately triggered an accumulation of γH2AX, a well-recognized marker of DNA double-strand breaks. Additionally, we established ectopic expression of hotspot mutant p53 in H1299 cells. Introduction of p53 R175 H promoted olaparib resistance as single-agent treatment, but the synergy between olaparib and MK-8776 was still achievable and the region of synergy was produced by lower combination concentrations. These data provide insight into how Chk1 inhibition could be effectively targeted and confer sensitivity to olaparib toward p53-deficient and HR-proficient cancers.